DNA Methylation-Based Age Prediction and Telomere Length Reveal an Accelerated Aging in Induced Sputum Cells Compared to Blood Leukocytes: A Pilot Study in COPD Patients - Campisi, Manuela; Liviero, Filippo; Maestrelli, Piero; Guarnieri, Gabriella; Pavanello, Sofia (Frontiers in Medicine, 2021)
Aging is the predominant risk factor for most degenerative diseases, including chronic obstructive pulmonary disease (COPD). This process is however very heterogeneous. Defining the biological aging of individual tissues may contribute to better assess this risky process. In this study we examined the biological age of induced sputum (IS) cells, and peripheral blood leukocytes in the same subject, and compared these to assess whether biological aging of blood leukocytes mirrors that of IS cells. Biological aging was assessed in 18 COPD patients (72.4±7.7 years; 50% males). We explored mitotic and non-mitotic aging pathways, using telomere length (TL) and DNA methylation-based age prediction (DNAmAge) and age acceleration (AgeAcc) [i.e., difference between DNAmAge and chronological age]. Data on demographic, life style and occupational exposure, lung function, clinical and blood parameters were collected. DNAmAge (67.4±5.80 vs 61.6±5.40 years; p=0.0003), AgeAcc (-4.5±5.02 vs -10.8±3.50 years; p=0.0003) and TL attrition (1.05±0.35 vs 1.48±0.21 T/S; p=0.0341) are higher in IS cells than blood leukocytes in the same patients. Blood leukocytes DNAmAge (r=0.927245; p=0.0026) and AgeAcc (r=0.916445; p=0.0037), but not TL, highly correlate with that of IS cells. Multiple regression analysis shows that both blood leukocytes DNAmAge and AgeAcc decrease (i.e., younger) in patients with FEV1% enhancement (p=0.0254 and p=0.0296) and combined inhaled corticosteroids (ICS) therapy (p=0.0494 and p=0.0553). In conclusion, new findings from our work reveal a differential aging in the context of COPD, by a direct quantitative comparison of cell aging in the airway with that in the more accessible peripheral blood leukocytes, providing additional knowledge which could offer a potential translation into the disease management.